2016
DOI: 10.22502/jlmc.v4i1.87
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perinatal Outcome of Breech Presentation between Vaginal Delivery and Cesarean Section

Abstract: Introduction: Many times, parturient opt for labour and vaginal breech delivery even after informing increased perinatal risks. Vaginal breech deliveries are undertaken with the reasons like avoidance of cesarean section in next pregnancy, null risk of operative and anesthetic hazards, ability to resume early all household works after vaginal birth, etc. The purpose of this study is to compare the perinatal outcome of breech deliveries in singleton breech presentation between vaginal breech delivery and cesare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
2
3
1
Order By: Relevance
“…Large population based studies are not available to quote the incidence of breech deliveries in our setup. Hospital-based studies conducted in different tertiary level hospitals have reported the breech delivery incidence of 1.9–2.5% [ 11 , 12 ], similar to the incidence reported in our study. But this is slightly lower than the overall incidence of 3–5% [ 1 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Large population based studies are not available to quote the incidence of breech deliveries in our setup. Hospital-based studies conducted in different tertiary level hospitals have reported the breech delivery incidence of 1.9–2.5% [ 11 , 12 ], similar to the incidence reported in our study. But this is slightly lower than the overall incidence of 3–5% [ 1 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis reported a very high perinatal mortality among vaginal breech deliveries compared to other studies [ 11 , 12 , 15 ]. Mortalities were higher among those with gestation more than 40 weeks, or among babies weighing less than 2500 grams as compared to those with birthweight ≥2500 grams (21.05% versus 4.62%; P =0.043).…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…This study was aimed at determining the prevalence and perinatal outcomes of singleton breech delivery at a tertiary level hospital in Nepal. The prevalence of breech presentation in our study was higher than that reported by previous studies conducted in Nepal (1.9-3.1%), 10,13,14 but it was less than the prevalence reported in Ethiopia 5 and Malaysia. 6 Our centre is a tertiary level hospital where significantly large number of cases of high-risk pregnancy including abnormal presentations are referred in, which might be the reason for higher incidence of breech in comparison to previous national studies.…”
Section: Discussioncontrasting
confidence: 85%
“…Nulliparous women were more likely to deliver by cesarean section. 4 Another study in Patan Academy of Health Sciences concluded that in well-selected cases, the neonatal outcome following assisted vaginal breech delivery and caesarean section may not be different. 5 Adverse perinatal outcome in planned vaginal breech labor at term is associated with fetal growth restriction, oligohydramnios, previous cesarean delivery, gestational diabetes, nulliparity and epidural anesthesia.…”
Section: Introductionmentioning
confidence: 99%